1982
DOI: 10.1164/arrd.1982.125.5.544
|View full text |Cite
|
Sign up to set email alerts
|

Noncomparability of Longitudinally and Cross-sectionally Determined Annual Change in Spirometry1-3

Abstract: Annual decline in lung function determined longitudinally is often compared with predicted decline determined cross-sectionally. To test this comparison, spirometric data were collected 5 times over 5 yr from 52 adult male Caucasians. The age regression coefficient for FEV1 and FVC, determined cross-sectionally at each visit, was more than twice the longitudinal annual change computed from the same data as the mean of the slopes of each subject's regression lines. The discrepancy persisted even when the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
2
9

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 0 publications
2
58
2
9
Order By: Relevance
“…In contrast, the FVC of a 60 year old man decreased by 0.6-0.7 l, with parallel trends in FEV 1 . The secular trend to a faster ageing of male FEV 1 was confirmed in longitudinal data, and cannot, thus, be dismissed as an artifact of altered population demographics or curvilinearity of the ageing process.…”
Section: Data Interpretationmentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast, the FVC of a 60 year old man decreased by 0.6-0.7 l, with parallel trends in FEV 1 . The secular trend to a faster ageing of male FEV 1 was confirmed in longitudinal data, and cannot, thus, be dismissed as an artifact of altered population demographics or curvilinearity of the ageing process.…”
Section: Data Interpretationmentioning
confidence: 85%
“…In urban populations, longitudinal estimates of lung function ageing have been both greater [14], and smaller [1,4,20] than cross-sectional values, depending on the relative strengths of the various factors biasing the two estimates. In the present study, the longitudinal data suggested a curvilinearity of ageing.…”
Section: Data Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous longitudinal studies have established that FEV 1 normally declines 20-30 milliliters per year (ml/yr) in nonsmokers and 40-50 ml/yr in smokers. (31)(32)(33) Additional factors unrelated to work can cause this decline to be greater than expected (e.g. respiratory infections, air pollution), as can work exposures.…”
Section: <45 <51mentioning
confidence: 99%
“…This correction is not only crucial for monitoring patients with chronic lung disease and to evaluate individual therapeutic interventions, but is also important in longitudinal clinical trials where indices such as forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) are often primary end-points. Correction for lung growth is usually achieved by expressing lung function parameters as a percentage of predicted (% pred), although predictions derived from cross-sectional studies may not accurately reflect lung growth within an individual [1,2].…”
mentioning
confidence: 99%